Damage Evolution Characteristics of Rock Salt under Different Stress Conditions - Chunping Wang; Jianfeng Liu; Lu Wang (Advances in Civil Engineering)
Understanding the damage evolution characteristics of rock material is essential to the long-term stability and safety analysis of the underground facility. In this study, a series of cyclic loading tests under tensile or compressive stresses are conducted to investigate the damage evolution, deformation, peak strength, and failure pattern of rock salt. A special attention is paid on the microcracking process by using a 3D acoustic emission (AE) test system. The laboratory tests show that the damage degree of rock salt under compression is the highest, followed by the damage in the direct tensile test. The lowest value of damage is determined by using the Brazilian test. The damage degrees where the damage rate starts to decrease are about 0.83 in the direct tensile test, about 0.75 in the Brazilian test, and about 0.91 in the compression test. The failure mode of rock salt changes from the tensile mode in the uniaxial compression test to the compression-shear mode in the confined compression test at low confinement. But from the confining pressure of 15 MPa, the rock salt displays great plastic dilatant distortion and without appreciable macroscopic fractures. Accordingly, with increasing confining pressure, the positions where the rapid increase in cumulative AE counts occurs and where the AE event with high energy appears are changed, from the beginning of the test at low confinement to the postpeak stage of the test at high confinement.